Skrining Kesehatan Mental dan Intervensi Non-Farmakologis dalam Pelayanan Antenatal pada Ibu Hamil: Tinjauan Sistematis - Susi Irianti; Mirza Fathan Fuadi; Sri Ratna Ningsih; Indah Puspitasari; Sri Achadi Nugraheni (Faletehan Health Journal, 2026)
Perinatal mental health disorders represent a significant global public health challenge, contributing directly to the risks of preeclampsia, preterm birth, and impaired fetal cognitive development. Globally, the prevalence of perinatal depression was estimated at 11.9 percent; however, in Indonesia, maternal anxiety rates were remarkably high, reaching 43.2 percent. This study aimed to analyze early detection strategies and non-pharmacological interventions that can be directly integrated into routine antenatal care. This systematic review followed the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) protocol by searching the literature on Scopus and PubMed databases. Inclusion criteria include peer-reviewed studies for the period 2020–2025 that focus on the prevalence, screening, and non-pharmacological interventions of pregnant women's mental health. The methodological quality of the study was assessed with the Joanna Briggs Institute (JBI) Critical Appraisal Checklist. Out of a total of 5,206 articles identified, 11 medium to high quality articles were selected for analysis. The findings indicated that the use of validated screening instruments and digital innovations, such as artificial intelligence, can accurately predict depression risk. Mindfulness interventions are effective for daily stress regulation, while cognitive behavioral therapy remains the primary standard for more severe clinical cases. This study emphasized the vital importance of digitalizing screening instruments integrated with electronic health records and enhancing the competence of midwives as mental health facilitators to reduce maternal morbidity nationwide.